COMMUNITY BENEFITTING THROUGH TOURISM (CBTT DASTA MODEL) AN INTEGRATED APPROACH - Pimapunsri, Punnee; Wisansing, Jutamas (RMUTT Global Business and Economics Review, 2022)
Community based tourism (CBT) has been used as a participatory approach to achieve a better quality of life for local communities. This paper synthesized extensive information on impact evaluations and indicators that can be applicable to measure various aspects of social, economic and environmental sustainability at a community level. Incorporating the existing approaches with lessons learned from a pilot project in 6 designed areas in Thailand, an integrated monitoring system called “linkages & leakages” has been developed. The purpose of this research was to look into the structure and function of a tourism promotion club, tourism management as well as the administration of tourism-related income and benefits (CBTT Model). A comprehensive and local friendly tool was leveraged by a multi-stakeholder’ co-creation and facilitated by the Designated Areas for Sustainable Tourism Administration (DASTA). It has been designed as a locally owned and led process for monitoring, managing, and enhancing the sustainability of CBT initiatives. Three intertwined sustainable dimensions; ecologically, socio-culturally and economically sustainable and equitable environment enable community leaders to delineate the need for empowerment and capacity building programs, local sourcing strategies, starting up community enterprises and their social capital building structures (social networks and trust).